MANAGEMENT OF BCC IN A TERTIARY CARE CENTER OF MALWA REGION OF PUNJAB: A CASE SERIES - Dr. Sumit Jain; Dr. Tushar Bhati; Dr. Sadaf Ali Faisal; Dr. Ashlee Girdhar; Dr. Jatin Ghai (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Basal cell carcinoma, the most common type of skin cancer, arises from the basal cells of the skin's outer layer. The primary etiological factor in the development of basal cell carcinoma is exposure to UV light, particularly the UVB wavelengths. The great majority of patients with BCC (95%) are noted to be between 40 and 79 years of age. BCC most commonly occurred over orbital (28.2%) and nasal (26.7%) areas on the face. Treatment of BCC include wide local excision followed by reconstruction. 60 patients with primary BCC, who presented to OPD department of Plastic Surgery and referred from Oncology department of GGSMCH, Faridkot were included in the study with minimum follow up for 6 months. Approximately seventy percent of Punjab's population is directly or indirectly engaged in agriculture. In our study, the majority of cases (82%) belonged to an agricultural background with a history of prolonged sun exposure while working in the fields. The most common incidence was seen in the sixth and fifth decade of life (33.3% and 30.00% respectively). The most common site involved was nose (35.00%) followed by cheeks (21.67%) and eyelids and canthi (16.67%). 53.33% of defects were reconstructed using flaps, 25% using skin grafting and elliptical excision followed by primary closure was done for 21.67% of the patients. While split-thickness skin grafting is a simpler choice, it tends to result in unsightly scars as it heals. Local flaps, on the other hand, provide a superior match in terms of color and texture and also maintain sensitivity, making them an ideal choice for reconstructing facial defects.